(untitled) (Comprehensive Journal of Science, 2025)
The present study aimed to examine the relationship between demographic variables and biodiversity by clarifying the concepts of both biodiversity and demography, identifying the main types, categories, and characteristics of biodiversity, and highlighting its role and relevance in secondary education. The study employed a descriptive-analytical method and was conducted on a random sample of 31 male and female students from the second grade of Zolten Secondary School during the period from December 30, 2024, to April 17, 2025. Data were collected using a questionnaire developed in light of the study’s objectives and research questions, and analyzed through frequencies, percentages, and graphical representations. The results revealed that environmental diversity ranked first with a weighted mean of (2.734), followed by genetic diversity (2.710), species diversity (2.702), and cultural background (2.621). Furthermore, Spearman’s correlation coefficient indicated a moderate positive relationship between biodiversity in the biology curriculum and cultural background, with a statistically significant value of (0.019) and a correlation coefficient of (0.418). The study recommends reducing human activities that negatively impact biodiversity, such as pollution, overhunting, and habitat destruction, in addition to promoting environmental awareness and education among students.